The Role of The Community In Creating A Village Conscious Of Religious Harmony In Tulungrejo Village, Bumiaji District, Batu City - Yusuf, Nurbani; Wibowo, Arif Prasetyo; Zuriah, Nurul; Sovia Sasmita, Nazathusohiroh (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2024)
The objectives of this study are (1) analyzing and describing the role of the community, (2) analyzing and describing the obstacles faced by the community, (3) analyzing and describing solutions to face obstacles in realizing a Religious Harmony Awareness Village in Tulungrejo Village, Bumiaji District, Batu City. This research uses a descriptive qualitative approach with a case study research design. This research was conducted in Tulungrejo Village, Bumiaji District, Batu City. Data collection in this study used structured interview techniques, passive participant observation of core informants and documentation with data sources obtained based on primary and secondary data. The data in this study is in the form of administrative data and local community activities. Data analysis in this study uses modified data analysis and interactive models by checking the validity of findings through credibility, transferability, dependability, and confirmability tests. To obtain reliable data, validation is carried out with source triangulation techniques. The result of this research is the contribution of the local community through mutual assistance and participation in community activities, especially in inter-religious activities. The obstacles in realizing the Religious Harmony Awareness Village are the fanaticism of the community in small groups who are less tolerant of differences between religious communities. The solution to overcome these obstacles is through the application of mutual openness and respect for each other.